Niños y adolescentes tras el visor de la cámara: experiencias de alfabetización audiovisual - Aguaded Gómez, José Ignacio; Sánchez Carrero, Jacqueline (Estudios sobre el Mensaje Periodístico, 2008)
This paper shows the results of a successful research about media literacy in Spanish America. Cities as New York, Buenos Aires, Madrid... are linked in a virtual way as educational headquarters where children and teenagers learn the keys to audiovisual knowledge. Opposite to an official media literacy system, groups of children everywhere begin to access to educational experiences with video and television. There is an increasing interest for teaching them what the world behind the camera is like, in order, not only to make them live that incredible experience, but also to teach them how to be critical viewers in a world full of screens.
Keywords: Media Literacy; Media education; Audiovisual document; Criticism; Media literacy; Production